Going Deeper with New Testament Greek: An Intermediate Study of the Grammar and Syntax of the New Testament = Uglubljajasʹ v grečeskij jazyk Novogo Zaveta - Lavrushko, Volodymyr (Bogoslovskie razmyšlenija, 2017)
Going Deeper with New Testament Greek is an intermediate NT Greek grammar, written by well-known NT professors Andreas J. Köstenberger (Southeastern Baptist Theological Seminary), Benjamin L. Merkle (Southeastern Baptist Theological Seminary), and Robert L. Plummer (The Southern Baptist Theological Seminary). The book is aimed at the needs of both intermediate Greek students and teachers.Going Deeper with New Testament Greek: An IntermediateStudy of the Grammar and Syntax of the New Testament.By Andreas J. Köstenberger, Benjamin L. Merkle, and RobertL. Plummer. N ashville: B&H Academic, 2016, ix + 550pp.;ISBN 978-1-4336-7908-7; 49.99 USD.** The review received on 13.12.2016; approved for publication 20.12.2016.